Aquaculture Law and Policy - VanderZwaag, David L.; Chao, Gloria (Routledge Advances in Maritime Research, 2006)
The aquaculture industry is fast expanding around the globe and causing major environmental and social disruptions. The volume is about getting a 'good governance' grip on this important industry. The book highlights the numerous law and policy issues that must be addressed in the search for effective regulation of aquaculture. Those issues include among others: the equitable and fair assignment of property rights; the design of effective dispute resolution mechanisms; clarification of what maritime laws apply to aquaculture; adoption of a proper taxation system for aquaculture; resolution of aboriginal offshore title and rights claims; recognition of international trade law restrictions such as labeling limitations and food safety requirements; and determination of whether genetically modified fish should be allowed and if so under what controls. This book will appeal to a broad range of audiences: undergraduate and postgraduate students, academic researchers, policy makers, NGOs, practicing lawyers and industry representatives.